Limited loan rate differentiation, guanxi, loan size and loan maturity in the Chinese bank credit market - Matthews, Kent; Yin, Wei (2020)
Since 2004, China has partially liberalized loan rate setting by the banks, but loan rates remain stubbornly within narrow bounds. We argue that competition in the loan market is signalled through the variation of loan deal terms and loan maturity rather than loan rates. We examine the determinants of loan deal conditions in terms of size and maturity. This paper focuses on the role of single firm-bank relationships in determining loan deal conditions as evidence of guanxi in Chinese banking market. Commercial loan deal terms of listed companies are matched to provider banks over the period 1999–2012 and sub-sample estimation for the pre-2004 and post-2004 periods confirm a change in the bank-firm-loan relationship. We find that single firm-bank relationships are associated with larger loan size and longer loan maturity in the pre-liberalization period but that this relationship has weakened in the liberalization period.